PENINGKATAN KOMPETENSI MENULIS CERITA PENDEK MELALUI PENGALAMAN DIRI SENDIRI PADA SISWA KELAS V SD NEGERI 101901 LUBUK PAKAM TAHUN PEMBELAJARAN 2024-2025 - Dwi Nofita Sari; Risnawaty; Sutikno; Rahmat Kartolo; Sri Ulina Beru Ginting (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to improve short story writing competence in fifth grade students of SD Negeri 101901 Lubuk Pakam through the use of personal experiences as the main source in developing ideas. This study uses a descriptive design that aims to collect quantitative data related to students' writing abilities in four main aspects: idea development, characterization of characters, use of plot and conflict, and language and grammar. A total of 35 students participated in short story writing activities based on personal experiences, the results of which were assessed using a rubric that had been prepared by researchers and Indonesian language teachers. The results showed that the average writing ability of students was 90, with the percentage of writing ability per aspect as follows: idea development (85%), character characterization (80%), use of plot and conflict (78%), and language and grammar (82%). These findings indicate that students find it easier to develop ideas and character traits when writing about personal experiences, although some students still have difficulty in organizing complex storylines and using good language. Based on these results, it is concluded that the use of personal experiences as writing materials can significantly improve students' writing skills, in line with the theory that personal experiences can motivate and increase student involvement in writing activities. This study also found that short story writing skills require continuous practice so that students can be more skilled in organizing ideas, building plots, and composing language well. The implication of this study is the importance of teacher guidance in honing students' writing skills, especially in determining ideas, building characters, and composing interesting stories.